A novel dextrin produced by the enzymatic reaction of 6-α-glucosyltransferase. I. The effect of nonreducing ends of glucose with by α-1, 6 bonds on the retrogradation inhibition of high molecular weight dextrin. Issue 7 (9th April 2021) - Yasuda, Akiko; Miyata, Manabu; Sano, Osamu; Sogo, Tatsufumi; Kishishita, Seiichiro; Yamamoto, Takuo; Aga, Hajime; Yamamoto, Koryu
ABSTRACT: We prepared a high-molecular-weight modified dextrin (MWS-1000) from a partial hydrolysate of waxy corn starch with a weight average molecular weight of 1 × 10 6 (WS-1000) using Paenibacillus alginolyticus PP710 α-glucosyltransferase. The gel permeation chromatography showed that the weight average molecular weight of MWS-1000 was almost the same as that of WS-1000. The side chain lengths of WS-1000 and MWS-1000 after isomaltodextranase digestion were also shown to be similar to each other by high-performance anion exchange chromatography with pulsed amperometric detection. Since MWS-1000 confirmed the presence of α-1, 6 bonds by enzyme digestibility, methylation, and 1 H-NMR analyses, it was presumed that the structure of MWS-1000 was based on the introduction of α-1, 6 glucosyl residues at the nonreducing ends of the partial hydrolysate of waxy corn starch. Furthermore, the MWS-1000 solution was not retrograded even during refrigerated storage or after repeated freeze–thaw cycles. Graphical Abstract: